Identification of Worm In Digestive Tract of Consumed Cattle Egret (Bubulcus ibis) In Ujung Pangkah, Gresik - Nisa’ Rachmaningtyas Putri; E Djoko Poetranto; Nunuk Dyah Retno Lastuti; Setiawan Koesdarto; Bambang Sektiari Lukiswanto; Kusnoto Kusnoto (Universitas Airlangga, 2018)
Ujung Pangkah, Gresik was became the most habitat of fowls such as Cattle egret (Bubulcus ibis). The aim of this research were to find out the type of worm that infected digestive tract of Cattle egret (Bubulcus ibis) in Ujung Pangkah, Gresik. The examination of worm in digestive tract was done by dissection and fecal examination. The identification based on morphological of the eggs and worms. The samples of digestive tract organ collected from restaurant that preserve Cattle egret as a main menu. Whereas the fecal sample collected by swab from the intestine. Cattle egret (Bubulcus ibis) has positive infection by worm parasite if there were worm or egg inside the digestive tract. Fecal samples were examined by native, sedimentation, coconut-sugar floating method and EPG counting with Lucient Brumpt. And the worm morphology from dissection of digestive tract would be identify with source book, journal, and discussed with supervisor. The result showed that 20 of digestive tract dissection and 20 fecal samples, there were three types of worm, Contracaecum sp., Cosmocephalus sp., Capillaria sp. and egg of Contracaecum sp. with 200 EPG